The design and testing of a kW-class free-piston Stirling engine for micro-combined heat and power applications. (5th January 2020) - Park, Jiho; Ko, Junseok; Kim, Hyobong; Hong, Yongju; Yeom, Hankil; Park, Seongje; In, Sehwan
Highlights: Developed free-piston Stirling engine (FPSE) with a dual-opposed alternator. Described design methodology of the FPSE. Demonstrated that the FPSE works. Explained output and dynamic characteristics of the FPSE. Abstract: This research paper describes the design methodology of the free-piston Stirling engine (FPSE) and its demonstration. The FPSE is equipped with a dual-opposed linear alternator. The design and experiment are mainly focused on understanding how the FPSE dynamically behaves. Based on the data obtained from experiments, the operational issues regarding the output and dynamic characteristics are discussed in detail. The FPSE can accept approximately 4.2 kW at the engine head with a temperature of 525 °C. As a heat source, city-supplied natural gas is used. The linear alternator stably produces 961 We -electricity at a resonance frequency of 60 Hz. The deduced efficiency of the linear alternator is 70–75% of the thermodynamic work generated by the engine. The integrated system, FPSE, has an overall efficiency of 23.0% when comparing the heat supplied to the electrical output. The FPSE was also proven with a direct connection to the grid, so it can generate and sell electricity back to the grid. The equipped resonant capacitor enables this by compensating for the power factor. The experiment results show that the design methodology is able to adequately explain the behavior of the FPSE.